Convenient and Rapid Synthesis of 3-Selenocyanato-4H-chromen-4-ones - Kosso, Anne Roly Obah; Broggi, Julie; Redon, Sébastien; Vanelle, Patrice (Synlett, 2018)
A sequential one-pot, simple and convenient method is described for the synthesis of 3-selenocyanato-4H-chromen-4-ones by addition, first of DMF-DMA and then of triselenodicyanide as electrophile.
Keywords: selenocyanate; chromones; triselenodicyanide; selenium dioxide; malononitrile; electrophile addition; oxidation; rearrangement